Total phenolics and antioxidant activity of a functional gel based on AÇAÍ (euterpe oleracea martius) pulp - Carvalho, Lucia Maria Jaeger (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The beneficial effects attributed to açaí and its derivatives are associated with its significant content of phenolic compounds, which has stimulated multiple/many researchers to identify these compounds and demonstrate their pharmacological properties, which include anti-inflammatory and antioxidant activities. The aim of this study was to determine the concentration of total phenolic compounds and the antioxidant activity of lyophilized pulps and functional gels of açaí. The antioxidant activity was the determining variable for the choice of the best formulation for the supplement. Pulp L exhibited higher antioxidant activity than the others according to the DPPH method, as well as higher content of total phenolic compounds. For the antioxidant activity, gels 3 and 4 did not differ significantly for the DPPH method, whereas in the ORAC method, gels 1 and 3 showed greater Trolox equivalents. It was concluded that gels 3 and 4 which had higher concentrations of lyophilized açaí pulp, showed higher concentrations of total phenolic compounds and consequently higher antioxidant capacity as demonstrated by the two methods applied and by the results obtained in the statistical analysis. Functional açaí gel may be used by adults who are involved in physical activities to reduce oxidative stress.